Organizational Performance: The Role of Enterprise Resource Planning and Supply Chain Management - Muthia Roza Linda; Gesit Thabrani; Suhery Suhery; Riza Yonita; Thesa Alif Ravelby; Vera Pujani; Alizar Hasan (AFEBI Management and Business Review, 2022)
Technological advances require companies to follow and adapt to technological developments and require companies to move with existing changes. Companies need a strategy to have a competitive advantage and improve organizational performance in dealing with these conditions. The study empirically tested the effect of mediating supply chain management (SCM) implementation on the relationship between Organizational performance and enterprise resource planning (ERP). The sample of this study were employees of PT. Semen Padang is involved in the supply chain management process and runs an enterprise resource planning system with 100 employees. The results of data processing using PLS-SEM showed a positive and significant effect in the direct relationship between ERP to SCM and SCM to performance. Furthermore, SCM mediates the relationship between ERP and company performance.